Influence of water deficit during different growth and developmental stages on the contribution of stored pre-anthesis assimilates to grain in selected durum and bread wheat genotypes - Moayedi, Ali Akbar; Boyce, Amru Nasrulhaq; Barakbah, Syed Shahar (American-Eurasian Network for Scientific Information, Jordan, 2009)
Under water deficit conditions, declining photosynthesis and the subsequent decline in assimilates during the grain filling stage can increase the contribution of pre-anthesis assimilates stored in the stems, to grain filling in order to prevent severe reduction in grain yield. Results of the present study, which tested five durum and bread wheat genotypes under four irrigation regimes in different growth and developmental stages, have shown that apart from the contribution of pre-anthesis assimilates to grain filling, which increased during the one-leaf until grain filling period under water deficit, dry matter translocation and dry matter translocation efficiency decreased at the floral initiation to grain filling stage. The remobilization contribution of pre-anthesis assimilates increased by 20 under water limitation during grain filling compared to optimum irrigation. In addition to this, genotype G2 (durum wheat) and cultivar G3 (bread wheat) exhibited the highest contribution of preanthesis assimilates to grain filling, which was associated with longer day to the heading and the plant height under the optimum moisture conditions. Furthermore, the spike dry weight, spike harvest index and spike partitioning coefficient were also higher in the G2 and G3 genotypes. Â© 2009, INSInet Publication.